Метод построения семантически эквивалентных состояний неоднородных баз данных - Танянский, С. С. (НТУ "ХПИ", 2013)
Propose a method of constructing a set of possible states of a database by modifying the structure of the data. The conditions of the permitted operations and introduce the operators of state transition of the database. Suggest appropriate algorithms and prove their correctness, adequacy and effectiveness.
Keywords: семантика данных; модификация структуры; целостность данных; правило логическое